Penerapan model pembelajaran kooperatif tipe team game tournament (TGT) terhadap hasil belajar shooting sepakbola - Azwira, Azrul; Atiq, Ahmad; Hidasari, Fitriana Puspa; Yunitaningrum, Wiwik; Triansyah, Andika (Jurnal Porkes, 2023)
The problem of this research is whether the application of the cooperative learning model of the team game tournament type can improve the learning outcomes of shooting football. The purpose of this study was to determine the learning outcomes of shooting football for students through a team game tournament cooperative learning model. The method in this study uses a class action research method. The subjects in this study were class VIII students of SMP Negeri 25 Pontianak, totaling 15 boys and 10 girls. Data collection techniques in this study used observation techniques and assessment rubrics. Data analysis uses descriptive percentages. The results of this study showed an increase in learning outcomes in shooting football, where classical completeness in learning to shoot soccer increased by 40%. At the pre-cycle stage, only 44% of students were able to exceed the KKM, then at the first cycle stage it increased to 64%, but these results still had to be improved so that the research continued to the second cycle stage. The results show an increase of 84%, this result meets classical completeness (70%). The conclusion in this study is that there is an increase in learning outcomes in shooting football through the application of a team game tournament cooperative learning model